The effectiveness of barrier wall for residential along highway in Malaysia / Siti Nur Syamimi Ab Karim - Ab Karim, Siti Nur Syamimi (2015)
Traffic noise pollution is an annoyance and also can be a significant short and long-term health hazard to the human. The source of the traffic noise pollution is from transportation systems, motor vehicles, road surface condition and also traffic flow speed. The aim of this study is to highlight the effectiveness of noise barrier wall for residential along highway in Malaysia. The purpose of this study is to determine the barrier wall as the structure to minimize the sound level disturbance to the receiver. This research is located at residential area at Highway Utara Selatan at Perak that provided by noise barrier wall. The methodology of this research is by using sound level meter and distributes the questionnaire to the resident to evaluate the opinions of the residents about road traffic noise and sleep disturbance towards publics. The noise pollution paper is also to identify the guidelines for barrier wall implementation in residential area to restrict noise, proved by measure effectiveness of barrier wall at residential area by using sound level meter and overcome for to propose the suitable implementation of barrier wall construction for residential. The results of the data analysis are based on the planning guidelines for environmental noise limit and control by Department of Environment Malaysia (JAS).